ANALISIS MANAJEMEN RISIKO PADA IMPLEMENTASI JAMINAN PRODUK HALAL DI INDONESIA - Panglima Thariq Al Huda (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The Law 33/2014 about Halal Product Assurance has made significant changes to industry in Indonesia. Initially, the requirements for halal certified products were voluntary, it become mandatory in accordance with article 4 of the Law. The implication is Products that enter, circulate, and traded in the territory of Indonesia must Halal certified. The Indonesian regulator about halal is Halal Product Assurance Body or known as BPJPH. Many incidents occurred regarding halal product guarantees in Indonesia before the existence of BPJPH which one is non-transparency. This research adopting a literature review. The results of the research are need to be mitigated holistically. Through the authorities possessed by the government, it is able to provide policies that are in favor of MSEs, for example providing free halal certificates through self declare. In addition, the government also have the power to provide solutions to the existing problems such as the extortion by organizations to the lawful abroad by granting temporary status. There is no doubt that the government can implementing halal Indonesia for world community